Review on the theory of moving reaction boundary, electromigration reaction methods and applications in isoelectric focusing and sample pre-concentration - Cao, Cheng-Xi; Fan, Liu-Yin; Zhang, Wei (Analyst (London), 2008)
Since 1970, a series of systematic investigations have been performed on three modes of moving reaction boundaries (MRBs), viz. moving precipitate boundary (MPB), moving neutralization boundary (MNB) and moving chelation boundary (MCB). So far, there has not been any review on them. Herein, we firstly review the MPB with respect to its velocity, product concentration, elution displacement, stacking effect, separation effect, judgment expressions and related procedures. We then make a review on the MNB about its theory, demonstration, improvement, and uses in isoelectric focusing (IEF), sample stacking, MNB-based stacking mechanisms and relevant computer simulations. We further give a review on the MCB regarding the relevant theory, verifications, and applications in EDTA-based sweeping and computer simulation. Finally, we give an outlook on the MRB study. More than 150 references are cited.